The Development of Madurese Language Posters as a Medium for Preserving the Madurese Regional Language at Religious Tourist Sites - Zulkhaeriyah Zulkhaeriyah; Muhlis Tahir (Hasanuddin University, 2025)
This research aims to understand the conditions and strategies of using the Madurese language in the social life and to explore the usage and preservation of the Madurese language among teenagers of teenagers who are part of the youth community. The design of this research is a descriptive qualitative study by collecting visual repertoires. Data obtained from the linguistic landscape of the public space at the religious tourism site in Bangkalan, namely the Mosque and the Tomb of Syaikhona Cholil. We took some photo in tourism area for evidence that includes the use of language in public spaces and images of the linguistic landscape of the photographed tourist destinations. This research examines the posters at tourist attractions that are not yet in the Madurese language. These posters are revitalized into posters containing Madurese text accompanied by symbols and images, so that these posters can be read in two or three languages: Madurese, Indonesian, and English. The research results show that some of youth joined the Karang Taruna play a role in preserving the Madurese language as a cultural heritage, one of which is by creating Madurese language posters that are placed in the Madura tourist area. The Madurese language posters placed in various corners of the religious tourism area are very significant in preserving the Madurese language for visitors, especially local tourists from Madura Island.